2016
DOI: 10.21608/amme.2016.35210
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Electron Beam Welding Parameters of Dissimilar Joint of Aisi 304 Stainless Steel and Aisi 1020 Low Carbon Steel

Abstract: This paper presents the optimization of welding parameters of electron beam welded joint of dissimilar materials namely AISI 304 stainless steel and AISI 1020 low carbon steel (0.21% C.). Three main welding parameters were investigated. These parameters are welding current, focusing current, and welding speed. The optimization was based, from one hand, on microstructure analysis of both bead and heat affected zones, using optical and scanning electron microscopes, and, from the other hand, the evaluation of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They emphasized the importance of parameter study in narrowing the HAZ and increasing the strength of the welding region; according to the experimental design, they applied EBW for AA1350 alloy, a material with low weldability. Nasr El-Deen et al [16] focused on optimizing EBW parameters for AISI 304 stainless steel and AISI 1020 materials. As a result of the study, they reported that the energy of the beam current has a significant effect on the characteristic properties of the welded joint.…”
Section: Introductionmentioning
confidence: 99%
“…They emphasized the importance of parameter study in narrowing the HAZ and increasing the strength of the welding region; according to the experimental design, they applied EBW for AA1350 alloy, a material with low weldability. Nasr El-Deen et al [16] focused on optimizing EBW parameters for AISI 304 stainless steel and AISI 1020 materials. As a result of the study, they reported that the energy of the beam current has a significant effect on the characteristic properties of the welded joint.…”
Section: Introductionmentioning
confidence: 99%